The ultrastructure of the intramandibular gland in soldiers of the termite Machadotermes rigidus (Blattodea: Termitidae: Apicotermitinae) - Beránková, Tereza; Buček, Aleš; Bourguignon, Thomas; Arias, Johanna Romero; Akama, Pierre D; Sillam-Dussès, David; Šobotník, Jan (Arthropod structure & development, 2022)
Machadotermes is one of the basal Apicotermitinae genera, living in tropical West Africa. Old observations suggested the presence of a new gland, the intramandibular gland, in Machadotermes soldiers. Here, by combining micro-computed tomography, optical and electron microscopy, we showed that the gland exists in Machadotermes soldiers only as an active exocrine organ, consisting of numerous class III cells (bicellular units made of secretory and canal cells), within which the secretion is produced in rough endoplasmic reticulum, and modified and stored in Golgi apparatus. The final secretion is released out from the body through epicuticular canals running through the mandible cuticle to the exterior. We also studied three other Apicotermitinae, Indotermes, Duplidentitermes, and Jugositermes, in which this gland is absent. We speculate that the secretion of this gland may be used as a general protectant or antimicrobial agent. In addition, we observed that the frontal gland, a specific defensive organ in termites, is absent in Machadotermes soldiers while it is tiny in Indotermes soldiers and small in Duplidentitermes and Jugositermes soldiers. At last, we could also observe in all these species the labral, mandibular and labial glands, other exocrine glands present in all termite species studied so far.
Keywords: Termites; Isoptera; švábi; Animals; Microscopy, Electron, Transmission; Soldier caste; transmisní elektronová mikroskopie; zvířata; X-Ray Microtomography; rentgenová mikrotomografie; Cockroaches; Class III secretory cell; Exocrine organ; Mandibles; exokrinní žlázy; Exocrine Glands